Revisiting Task-based Language Teaching to TEYL: Evidence from Indonesian Young Learners - Metty Agustine P.; Emi Emilia; Didi Sukyadi (Universitas Negeri Semarang, 2025)
The study aimed to investigate the values of Task-based Language Teaching (TBLT) in teaching English in non-formal setting to fifteen young learners (YLs) from five schools in Tasikmalaya, West Java, Indonesia. The study has been informed by the theory of TBLT in English teaching. The study used qualitative case study research design at the data when collected through a phase of teaching of six meetings where the researcher acted as teacher and interviews with five participants. The data were analysed qualitatively using thematic analysis, in terms of TBLT implementation to assist YLs learn English and participants responses to the values of TBLT implementation. The results show that two themes occurred, involving 1) the implementation of TBLT and students’ learning which focuses more on the use of input-based tasks and 2) the students’ responses on the TBLT implementation including positive attitudes and challenges towards TBLT. The use of input-based tasks can enhance YLs’ vocabulary mastery and maintain their motivation to learn English. This is in line with the evidence that YLs are ready to learn English meaningfully when they have sufficient vocabulary input as a language element to learn a foreign language. It is recommended that TBLT be implemented in more diverse context in Indonesia.